Acupuncture inhibition of methamphetamine‐induced behaviors, dopamine release and hyperthermia in the nucleus accumbens: mediation of group II mGluR. (23rd January 2018) - Kim, Nam Jun; Ryu, Yeonhee; Lee, Bong Hyo; Chang, Suchan; Fan, Yu; Gwak, Young S.; Yang, Chae Ha; Bills, Kyle B.; Steffensen, Scott C.; Koo, Jin Suk; Jang, Eun Young; Kim, Hee Young
Abstract: Methamphetamine (METH) increases metabolic neuronal activity in the mesolimbic dopamine (DA) system and mediates the reinforcing effect. To explore the underlying mechanism of acupuncture intervention in reducing METH‐induced behaviors, we investigated the effect of acupuncture on locomotor activity, ultrasonic vocalizations, extracellular DA release in the nucleus accumbens (NAcs) using fast‐scan cyclic voltammetry and alterations of brain temperature (an indicator of local brain metabolic activity) produced by METH administration. When acupuncture was applied to HT7, but not TE4, both locomotor activity and 50‐kHz ultrasonic vocalizations were suppressed in METH‐treated rats. Acupuncture at HT7 attenuated the enhancement of electrically stimulated DA release in the NAc of METH‐treated rats. Systemic injection of METH produced a sustained increase in NAc temperature, which was reversed by the DA D1 receptor antagonist SCH 23390 or acupuncture at HT7. Acupuncture inhibition of METH‐induced NAc temperature was prevented by pre‐treatment with a group II metabotropic glutamate receptors (mGluR2/3) antagonist EGLU into the NAc or mimicked by injection of an mGluR2/3 agonist DCG‐IV into the NAc. These results suggest that acupuncture reduces extracellular DA release and metabolic neuronal activity in the NAc through activation of mGluR2/3 and suppresses METH‐induced affective states and locomotor behavior. Abstract : The effect of acupuncture on methamphetamine‐induced behaviors and the underlying mechanisms are unclear. The present study examined the effect of acupuncture on locomotor activity, ultrasonic vocalization, dopamine release and brain temperature in acute methamphetamine‐treated rats and possible mediation of mGluR2/3. Our findings suggest that acupuncture reduces extracellular DA release and metabolic neuronal activity in the NAc through activation of mGluR2/3 and suppresses methamphetamine‐induced affective states and locomotor behavior.